The War on War League: A South African Pacifist Movement, 1914-1915 - Hyslop, Jonathan (Scientia Militaria - South African Journal of Military Studies, 2016)
The outbreak of the First World War divided the South African Labour Party, a movement representing the country’s white working class. The party’s parliamentary delegation supported South African government’s participation in the war effort, but many leadership figures within the party and the trade unions disagreed with this stance. The dissidents formed an organization called the War on War League. In mid-1915, the anti-war activists left the party and formed the International Socialist League, a predecessor of the Communist Party of South Africa. The War on War League has conventionally been regarded as important only for its role in the eventual formation of the Communist Party. This article however contends that it needs to be understood in its own terms, as a pacifist movement, reflecting a political moment of resistance to the plunge into global war.